2014
DOI: 10.14687/ijhs.v11i1.2758
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of social capital and social networking of drug trafficking

Abstract: Transnational organized crime (TOC), such as drug trafficking, has been a sustained problem for society because of the visible impact on drug abuse that is evident in media coverage. However, research on the development of drug trafficking organizations through clandestine social networks has been limited. Consequently, this study applies Social Network Theory to significant aspects of drug trafficking-business economics and social networks inside drug trafficking groups. The analysis identifies similarities b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Drug abuse and drug dealing have their own networking patterns, which help sustain such activities [ 41 ]. Unlike highly organized networks of drug trafficking [ 51 ], in the context of the former drug abusers in the present study, the drug supply networks appeared to be fluid, loosely connected, non-hierarchical, and without physical infrastructure, as other scholars have mentioned [ 40 , 41 ]. Moreover, drug abuser networks allow the entry of members through the snowball effect (e.g., friends introducing their friends and acquaintances) [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Drug abuse and drug dealing have their own networking patterns, which help sustain such activities [ 41 ]. Unlike highly organized networks of drug trafficking [ 51 ], in the context of the former drug abusers in the present study, the drug supply networks appeared to be fluid, loosely connected, non-hierarchical, and without physical infrastructure, as other scholars have mentioned [ 40 , 41 ]. Moreover, drug abuser networks allow the entry of members through the snowball effect (e.g., friends introducing their friends and acquaintances) [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study identified trust as a determining factor for attaining access into drug abuser social networks. As Yeşilyurt [ 41 ] put it, to protect members in the networks from potential harm, “trusting the right person is the key” (p. 287). Trust has also been found to be a key in organized drug trafficking networks [ 51 ] and the familial illegal trading networks [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural features of dark networks may differ from the networks of mainstream governments, businesses, religions, or other forms of legitimate and non-covert social activity if dark network participants need to conceal their activities to prevent infiltration of the network by moles. Empirical analyses, however, point to many similarities in the network structures of dark and legitimate social networks, 1416 likely because to be useful for its members’ goals, both must perform much the same functions. The diffusion of information and beliefs can be viewed as one such core function that dark networks share with most other human social networks.…”
Section: Introductionmentioning
confidence: 99%